Virtually Connected, Socially Disconnected: The Impact of Online Game Addiction on Student Interaction - Aisyah Nur Farhana; Sara Sahrazad; Lira Erwinda; Rosada Rosada; Yuliana Yuliana (Jurnal Keilmuan Pendidikan, 2026)
This study aims to determine the effect of online games on the social interactions of students at An-Nur Junior High School Jakarta. The research method uses a quantitative approach with simple linear regression analysis. The results of the study indicate that online games have a significant effect on students' social interactions, as indicated by a significance value of 0.000 ≤ 0.05 so that H₀ is rejected and Hₐ is accepted. The regression equation obtained is Y = 28.868 + 0.543X with a coefficient of determination (R²) of 0.426. This means that 42.6% of the variation in students' social interactions is influenced by online gaming activities, while the other 57.4% is influenced by other factors outside this study.